River Bank Analysis in the Vicinity of Sebatik Island and Its Influence to Determine Boundary of Indonesia-Malaysia - Ardiawan Jati; Danar Pratomo (Geography Education Study Program, Universitas Kanjuruhan Malang, 2020)
Abstract: Sungai sebagai batas tercantum dalam Perjanjian Belanda-Inggris tahun 1915 dengan Peta Lampiran tanpa koordinat yang jelas. Ini merupakan kendala dalam melacak batas-batas di sungai karena yang mana sungai itu dinamis, perubahan bentuk dan tepi sungai dapat terjadi dalam kurun waktu lebih dari 100 tahun. Citra satelit Landsat multi-temporal yang diproses dengan kombinasi band (color composite) digunakan untuk mengamati posisi tepi sungai dari tahun 1989 hingga 2019 dengan interpretasi visual dan digitalisasi manual. Hasilnya, selama 30 tahun terjadi pergeseran di tepi sungai Sikapal dengan rata-rata 11,4 m di sisi kanan (Indonesia) dan 15 m di sisi kiri (Malaysia). Pergeseran rata-rata tepi sungai Tamboe adalah sisi kanan 25,1 m dan di sisi kiri 8,8 m. Pergeseran ini relatif kecil karena di sekitar sungai Sikapal dan Tamboe banyak ditumbuhi oleh hutan bakau yang dapat memperlambat laju erosi. Tepi sungai pada tahun 1989, 1999, 2009 dan 2019 digunakan sebagai dasar penentuan batas Indonesia-Malaysia menggunakan pendekatan tiga tahap. Hasilnya, ada perbedaan dalam bentuk garis batas meskipun kecil. Namun, wilayah sungai Indonesia dan Malaysia masih memiliki rasio proporsional 1: 1,03 pada tahun 1989, 1999, 2009 dan 2019. Meskipun rasio tersebut sama, luas sungai telah meningkat sebesar 0,08-0,11 km2. Abstrak: River as the boundary is listed in the 1915 Netherland-British Agreement with its Annex Map without any clear coordinates. This is an obstacle in tracing boundaries in the real river because where river is dynamic, changes in the river shape and river bank can occur in more than 100 years. Multi-temporal Landsat satellite imagery processed with a combination of bands (color composite) is used to observe the position of the river bank from 1989 to 2019 with visual interpretation and manual digitization. As a result, over 30 years there was a shift in the Sikapal river bank with an average of 11.4 m on the right side (Indonesia) and 15 m on the left side (Malaysia). The average shift of the Tamboe river bank is the right side 25.1 m and on the left side 8.8 m. The shift is relatively small because around the Sikapal and Tamboe rivers banks are overgrown by mangrove forests which can slow down the rate of erosion. River banks in 1989, 1999, 2009 and 2019 were used as a basis for delimitation of the Indonesia-Malaysia boundary using a three-stage approach. As a result, there are differences in the shape of the boundary line although it is small. However, the river area of Indonesia and Malaysia still has a proportional ratio of 1: 1.03 in 1989, 1999, 2009 and 2019. Although the ratio is the same, the area of the river has increased by 0.08-0.11 km2.